Christmas with the Queen : [large type] a novel - Gaynor, Hazel (William Morrow Large Print, an imprint of HarperCollins Publishers, 2024)
December 1952. While the young Queen Elizabeth II finds her feet as the new monarch, she must also find the right words to continue the tradition of her late father's Christmas Day radio broadcast. But even traditions must evolve with the times, and the queen faces a postwar Britain hungry for change. As preparations begin for the royal Christmas at Sandringham House in Norfolk, old friends--Jack Devereux and Olive Carter--are unexpectedly reunited by the occasion.